The Dialectical Interplay of Ikhtilāf al-Ṣaḥābah (Companions’ Disagreements): The Constructive Role of Diversity in Early Islamic Jurisprudence - Utami, Sinta Hardiyanti; Heryana, Esya; Fajriyah, Mutiara (Universitas Islam Negeri Alauddin Makassar, 2025)
This study examines the factors underlying juridical disagreements among the Prophet’s Companions, aiming to challenge the perception that such differences were inherently divisive and instead highlighting their constructive role in the development of Islamic jurisprudence. Using a qualitative descriptive-analytical approach based on library research, the study analyzes classical and modern sources to identify both internal factors, such as variations in linguistic interpretation, reasoning methods, and levels of knowledge, and external factors, including geographical, social, and political contexts, that shaped the Companions’ interpretations of the Qur’an and Hadith or guided their ijtihad when explicit scriptural evidence was absent. Case studies such as the ruling on triple divorce, the punishment for drinking khamr, and the timing of the ‘Asr prayer at Banu Qurayzah demonstrate the diversity of legal opinions that emerged in early Islam. The originality of this research lies in its emphasis on the dialectical interplay between internal and external dynamics, moving beyond simplistic views of disagreement as conflict. The findings imply that the Companions’ differences should be understood as intellectual diversity and tolerance within the classical fiqh tradition, offering valuable insights for contemporary discussions on Islamic legal thought.